(untitled) (International Journal of Food and Nutritional Sciences, 2022)
As it is known that language has 4 skills, viz listening, reading, writing and speaking. Among these listening and reading are passive skills and writing speaking are active skills. Once again they can be classified as receiver’s skills (L&R) and sender’s skills (w&sp) .Command in all these four skills can make a person perfect/proficient and judges the person’s position in the society. Only this kind of people can use language and expedited it in well manner.